New Poems, and Variant Readings - Stevenson, Robert Louis, 1850-1894; Osbourne, Lloyd, 1868-1947 (Salt Lake City, UT : Project Gutenberg, 1996)
"New Poems and Variant Readings" by Robert Louis Stevenson is a collection of poetry released in the early 20th century, specifically in 1918. This compilation includes poems that reveal Stevenson's private thoughts and feelings, some of which are deeply intimate and personal. The collection showcases a range of themes, with a notable focus on love, loss, nature, and the complexities of emotions, likely drawn from Stevenson's own experiences. The opening of the collection begins with a preface by Lloyd Osbourne, who emphasizes the significance of the poems and the gratitude owed to those who helped bring them to light. Osbourne suggests these works provide profound insights into Stevenson's emotional life, notably his love poems, which possess a unique sincerity despite their varied quality. As the reader delves into the opening poems, they encounter reflections on love's trials, the beauty of nature, and personal musings that illustrate the depth of Stevenson's poetic craft, inviting readers to explore the blend of melancholy and hope woven throughout his words. (This is an automatically generated summary.)
Release date is 1996-02-01
Transcribed from the 1918 Chatto & Windus edition by David Price
Keywords: Love poetry; Didactic poetry